Jak powstawał Fotosuplement do Słownika warszawskiego i co z tego wyszło - Wierzchoń, Piotr (Scripta Neophilologica Posnaniensia, 2018)
Jak powstawał Fotosuplement do Słownika warszawskiego i co z tego wyszło